Identifying Ambidexterity Behavior: The Role of Organizational Support and Career Adaptability to Optimizing Salesperson Performance - Priantama, Pramdigdya Sasliandri; Rostiana, Rostiana (International Journal of Economics Development Research (IJEDR), 2024)
Salesperson are considered as the frontline employees for companies in achieving superiority among other competitors and play an important role in the progress of a company. This study aims to determine whether organizational support and career adaptability plays a greater role in performance, either through direct relationships or through the mediation role of ambidexterity behavior. The high demands of work make salesperson need to display ambidexterity behavior in their work in order to improve performance effectiveness. Ambidexterity behavior refers to efforts to implement two strategic goals simultaneously, namely hunting orientation and farming orientation. When salespeople who have implemented ambidexterity behavior in their work, they aren’t only oriented towards sales, but will also position himself as the frontline who is ready to provide the best service to customers. The results of this study explain that career adaptability plays a greater role in performance when mediated by ambidexterity behavior.